2009
DOI: 10.2190/ag.68.2.c
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Older Men Report Low Stress Ratings? Findings from the Veterans Affairs Normative Aging Study

Abstract: We examined the interplay between three explanatory hypotheses for why older adults appear to rate their problems as less stressful than do younger adults: age-related differences in personality, in types of problems, and in the appraisal process-specifically, the number of primary stress appraisals. A sample of 1054 men from the Normative Aging Study (mean age = 65.02; range = 45 to 92) were interviewed about a problem in the past week. Personality did not mediate the effect of age on stress ratings. While ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…This does not seem to be due either to personality changes with age, or to the types of problems they face. Rather, we believe that older adults' greater experience with many types of problems gives them a more balanced perspective on their daily stressors (Boeninger et al 2009). …”
Section: Dealing With Problemsmentioning
confidence: 96%
See 1 more Smart Citation
“…This does not seem to be due either to personality changes with age, or to the types of problems they face. Rather, we believe that older adults' greater experience with many types of problems gives them a more balanced perspective on their daily stressors (Boeninger et al 2009). …”
Section: Dealing With Problemsmentioning
confidence: 96%
“…For example, one older man in one of our NAS studies remarked that he used to get upset about little things, but now that he has high blood pressure, he can't afford to anymore (Aldwin, Sutton, Chiara, et al 1996). Older adults may be less likely to appraise situations as problematic (Boeninger et al 2009), which might account for both their lower levels of reported stress and sometimes better physical profiles under stress.…”
Section: Fema Andrea Boohermentioning
confidence: 99%
“…Thus, older adults appear less likely to appraise situations as problems, and are more likely to use minimalist strategies that deflect or decrease negative arousal (see Aldwin, 2007). Boeninger et al (2009) tested the appraisal part of this hypothesis and found that nearly all of the variance in older men’s ratings of the stressfulness of problems was due to age differences in primary appraisal processes concerning the type of problem the hassle posed (e.g., harm, threat loss, challenge, threat to others, or annoyance). Older men reported fewer appraisals of particular events, suggesting that they may be more likely to keep problems from multiplying across domains (Pearlin, Mullan, Semple, & Skaff, 1990), thus decreasing stress.…”
Section: Emotion Regulation and Agingmentioning
confidence: 99%
“…Specifi c types of major or chronic stressors may be more likely to occur in later life, including the death of social network members, disability and serious health conditions faced by the self and others, the loss of social connections due to role loss, relocation, or the health status of social network members or the self, and caregiving for a disabled or ill spouse (e.g., Boeninger, Shiraishi, Aldwin, & Spiro, 2009;Folkman, Lazarus, Pimley, & Novacek, 1987;Glass, Kasl, & Berkman, 1997). Financial stressors may also be common in later adulthood.…”
Section: Aging and Stress Experiencementioning
confidence: 99%